The Effect of Smartphone Addiction on Communication with Peers in Madrasah Tsanawiyah - Rikatul Khasanah; Nurussakinah Daulay (Jurnal Basicedu, 2022)
This study aims to determine the effect of smartphone addiction on communication skills with peers at MTs Nurul Hikmah Aek Gerger Sidodadi. The research method uses a quantitative approach. The number of samples in this study was 52% of the total population of 299 students, with further criteria that 155 students had smartphones. The data collection technique used a smartphone addiction scale and a peer communication scale. The results of this study indicate that there is a significant negative relationship between the influence of smartphone addiction and peer communication skills, this is based on the results of the analysis using the product-moment technique which obtained the value of rcount = -0.7118 < rtable = 0.159. In conclusion, the higher the use of smartphones, the lower the ability to communicate with peer students, and vice versa the lower the use of smartphones, the higher the ability to communicate with peer students.